THE ROLE OF CELEBRITY ENDORSERS ON SOCIAL MEDIA INFLUENCING CONSUMER PURCHASE DECISIONS ON WARDAH RENEWYOU SERUM PRODUCTS AT WARDAH BEAUTY STORE AEON MALL BSD SOUTH TANGERANG - Dipayanti, Kris; Gracia, Bunga Astra (Yayasan Education and Social Center, 2025)
This study aims to determine the Role of Celebrity Endorsers in influencing Consumer Purchasing Decisions. This study was conducted at the Wardah Beauty Store at Aeon Mall BSD Tangerang Selatan. The method used is an associative research method with a quantitative approach. With the population in this study around 206 consumers, the research sample obtained 67 respondents using the Slovin formula sampling with an error rate of 10%. Data Analysis Methods used for this study are validity test, reliability test, correlation coefficient test, simple linear regression test, determination coefficient test, and Hypothesis Test (t-test) using SPSS 25 calculations. The results of the study indicate that there is a positive and significant influence between Celebrity Endorser on Purchasing Decisions with the regression equation Y = 14.054 + 0.567 X can be interpreted that if later Celebrity Endorser increases by 1, then the average value of Purchasing Decisions each month will increase by 0.567 or each Price value by 10, the average value of Purchasing Decisions each month also increases by 5.67. The correlation coefficient value (R) of 0.644 means that there is a Strong relationship between Celebrity Endorser (X) and Purchasing Decisions (Y) and the coefficient of determination (R Square) obtained is 0.415. This means that Celebrity Endorser influences Purchasing Decisions by 41.5% and the remaining 58.5% is influenced by other variables not studied. The hypothesis test above-obtained t count> t table which is 6.784> 1.673, so it can be said to be positive, this is also reinforced by a significance value of 0.000 <0.10. This means that H0 is rejected and Ha is accepted, meaning there is a positive and significant influence between Celebrity Endorser and Purchasing Decision